The Community Perception Toward Health Quality Service Provided in Malaysia - Sekarrini, Cipta Estri; Puspanathan, Puspanathan (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The purpose of this research to find out about community perceptions toward health quality services provided by the Malaysia government. The type of research was used descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. The type of data in the form of primary and secondary data obtained from interviews with the public about the perception of health quality services provided by the Malaysia government. The results of the research obtained the data that community perceptions of health quality services provided by the Malaysia government to indigenous people with the migrant population were the same, the difference was that the financing of treatment for migrants was slightly more expensive than the indigenous population. Both in the royal hospital and in private hospitals. The Malaysian government sets Universal Coverage, that was, all citizens were guaranteed health services received by paying only 1 RM (Malaysian Ringgit) for treatment with a general practitioner and 5 RM for treatment with a specialist. However, severe illnesses were not included in this health financing system because it was expensive. In medicine must be ensured complete self-document so that treatment can run well.